A qualitative study of food sociality in three provinces of South China: social functions of food and dietary behavior - Yan, Youxuan; Petersen, Jindong Ding; Lin, Liuting; Chen, Juncai; Li, Xiyi; Ji, Guiyuan; Zhang, Fan (Frontiers in Nutrition, 2023)
Background Food sociality refers to the exploration of food production, exchange, distribution, and consumption and influences on cultural communication and social meaning. This study aimed to investigate food sociality in three provinces of South China to provide theoretical and practical evidence of food sociality in the region and to revise nutrition policies. Materials and methods We conducted a qualitative study comprising 25 experts in the fields of nutrition, sociology, food science, and agriculture from Hainan, Guangdong, and Guangxi Province by using a semi-structured in-depth interview, which included 28 pre-determined questions covering six topics. The interviews were conducted between November 2020 and March 2021. Verbatim transcripts were analyzed thematically using NVivo 11.0. Results Of the 25 experts, the mean age was 50.6 (SD = 8.4) years, 15 (60%) were male, and 22 (88%) held a master's degree or above. The analysis showed that food sociality in three provinces of South China mainly comprises social functions of food and dietary behavior. Regarding social functions of food, the experts expressed that food represents local culture (72%, 18 experts), presents social status and economic power (40%, 10 experts), and is central to special occasions, traditional customs, and etiquette activities (60%, 15 experts). In terms of social functions of dietary behaviors, the majority of experts indicated that food is a social communication tool (72% experts), has geographical characteristics (80% experts), and, to some extent, is used as a proxy for reward or punishment. Furthermore, festivals are one of the core elements of food sociality in the region, although food safety is a major concern. Some dietary behaviors, such as overindulgence in afternoon tea and encouraging drinking, may increase the risk of chronic diseases. Conclusion Food sociality in three provinces of South China is mainly related to the social function of food and dietary behavior. It is a combination of local culture, social status and economic power, traditional customs, rewards and punishments, geographical food preference, and social communication tools. The authors recommend increasing food safety at festivals and promoting healthy eating behaviors in order to improve the overall health of the population in this region.